Model SWAT (Soil and Water Assesment Tool) untuk Analisis Erosi dan Sedimentasi di Catchment Area Sungai Besar Kabupaten Banjar - Febrianti, Indah; Ridwan, Ichsan; Nurlina, Nurlina (Lambung Mangkurat University Press, 2018)
Erosion is a natural process that occurs naturally causing sedimentation in a stream. The transported sediment material can reduce channel capacity and increase the risk of flooding, as happened in the Big River Fishing Area, Karang Intan Subdistrict, Banjar District. Therefore it is necessary to determine the value of erosion and the latest sediment in order to be the basis of consideration of management actions. Watershed management analysis using hydrological model. Soil And Water Assessment Tool (SWAT) is one of the hydrological models that can be used to analyze erosion and sedimentation with parameters such as rainfall data, temperature, land cover, soil and slope. SWAT model simulation using land use data, soil, rainfall and climate data of 2016, the amount of sedimentation and erosion in Catchment Area of large river is 58,48 ton/ha/year and 4,82 ton/ha/year. The level of sedimency in the Catchment Area of the Great River which belongs to very low class is 1635,38 ha, low grade 57,31 ha, middle class 385,21 ha and very high class that is 3.221,48 ha. While the level of erosion that includes very light class of 2334,24 ha, lightweight 2.692.31Â ha and middle class area of 272.83 ha.